The importance of ISO management system standards in a scenario of profound changes caused by the Covid-19 pandemic to Brazilian companies - Anholon, Rosley; Pavan Serafim, Milena; Dibbern, Thais; Leal Filho, Walter (Brazilian Journal of Operations & Production Management, 2021)
Goal: The aim of this viewpoint is characterized by emphasizing the importance of the management standards of the International Organization for Standardization as an information base for improvements to Brazilian managers in a scenario of profound changes caused by the Covid-19 pandemic. Design / Methodology / Approach: Initially, a brief bibliographic research was carried out to base some information presented in the text. Later, the authors of this viewpoint discussed their ideas and established the reflections presented here, many of them based on their experiences and the Brazilian context. Finally, the final considerations were established. Results: The main reflections are directed in the sense that most Brazilian companies have felt harshly the consequences of the economic crisis resulting from the pandemic of Covid-19 and, in some way, they need to rethink some of their administrative practices. In this scenario of profound organizational changes, we believe that the management standards of the International Organization for Standardization can be characterized as an important knowledge base, since they present information of high credibility, widely debated by experts and that are easily accessible to Brazilian managers in different themes. Limitations of the investigation: Since it is a viewpoint, part of the information presented here are the perceptions and considerations of the authors. Practical implications: This viewpoint shows that the standards of the International Organization for Standardization can be used as an important tool for management systems focused on innovation and employee skills management. Originality / Value: We hope with this viewpoint to advocate for ISO management standards as important instruments of continuous improvement in a scenario of many organizational changes for Brazilian companies.